Preparation method of lithium iron phosphate, lithium iron phosphate, pole piece and battery

By regulating the particle size and ratio of the precursor mixed slurry in lithium iron phosphate batteries and adopting a three-stage sintering process, the problem of low energy density of lithium iron phosphate batteries is solved, and a comprehensive improvement of high compaction density and high magnification capacity is achieved.

CN120057881APending Publication Date: 2025-05-30湖北金泉新材料有限公司
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510060778.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-14
Publication Date
2025-05-30

AI Technical Summary

Technical Problem

The existing lithium iron phosphate batteries have low energy density and are difficult to improve compaction density and magnification capacity at the same time.

Method used

By preparing a precursor mixed slurry containing iron phosphate, lithium source and carbon source, and particle size control is performed on the particles to form a particle mixture of different particle sizes. After three-stage sintering treatment, lithium iron phosphate material with high compaction density and high magnification capacity is prepared.

Benefits of technology

The energy density improvement and cycle stability improvement of lithium iron phosphate batteries have been achieved, and the compaction density and magnification capacity are high.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005243562840000111
    Figure BDA0005243562840000111
Patent Text Reader

Abstract

The invention provides a preparation method of lithium iron phosphate, lithium iron phosphate, a pole piece and a battery, the preparation method of lithium iron phosphate comprises the following steps: preparing a precursor mixed slurry containing iron phosphate, a lithium source and a carbon source, carrying out particle size regulation and control on particles in the precursor mixed slurry, the particles A, the particles B, the particles C and the particles D meet the specific particle size relation proportion; mixing the particles A, the particles B, the particles C and the particles D according to the ratio of (1-50): (10-40): (20-50): (50-70) to obtain precursor mixed slurry, and drying the precursor mixed slurry to obtain an intermediate; the intermediate is subjected to three-stage sintering in a protective gas atmosphere, the sintering temperatures of the three-stage sintering are sequentially increased, lithium iron phosphate is prepared, in the three-stage sintering, the sintering temperature of the first-stage sintering is 300-450 DEG C, and the sintering time is not shorter than 1 hour. According to the preparation method of the lithium iron phosphate, the prepared lithium iron phosphate has relatively high compaction density and relatively high rate capacity at the same time, so that the energy density and the cycling stability of a battery taking the lithium iron phosphate as a positive electrode material are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of lithium batteries, and specifically relates to a preparation method of lithium iron phosphate, lithium iron phosphate, an electrode sheet, and a battery. Background Art

[0002] Lithium-ion batteries have the advantages of high power density, high energy density, long cycle life, low cost, and safety, and are considered an ideal choice for electric vehicles, hybrid electric vehicles, and plug-in hybrid electric vehicles. Lithium iron phosphate with an olivine structure has the advantages of high structural stability, good safety performance, moderate working voltage, good platform characteristics, and large theoretical capacity, and has gradually become a hot topic for battery researchers to compete in research.

[0003] Since lithium iron phosphate was developed for use as a cathode material for lithium batteries, good results have been achieved in the field of cathode battery materials. However, commercially available lithium iron phosphate has the problem of low energy density. Energy density has a great influence on the performance of lithium-ion batteries and is closely related to the specific capacity, efficiency, internal resistance, and battery cycle performance of the electrode sheet. At present, the industry mainly improves the energy density of lithium iron phosphate batteries through the following two ways: one is to improve the rate capacity of the material, that is, to improve the capacity retention ability at high charge and discharge rates; the other is to increase the tap density of the material, so as to store more energy under the same volume or weight. However, these two methods often conflict in practical applications, and it is difficult to simultaneously improve the tap density and rate capacity. Summary of the Invention

[0004] Aiming at the deficiencies of the prior art, the purpose of the present invention is to provide a preparation method of lithium iron phosphate, lithium iron phosphate, an electrode sheet, and a battery. By applying the preparation method of lithium iron phosphate, the obtained lithium iron phosphate can simultaneously have a high tap density and a high rate capacity, thereby improving the energy density and cycle stability of the battery using the lithium iron phosphate as a cathode material.

[0005] According to the first aspect of the present invention, there is provided a preparation method of lithium iron phosphate, including the following steps: preparing a precursor mixed slurry containing iron phosphate, a lithium source, and a carbon source, regulating the particle size of the particles in the precursor mixed slurry to obtain particles A, B, C, and D, and the average particle size D of particle A 50 Denoted by D 1 The average particle size D of particle B 50 Denoted by D 2 The average particle size D of particle C 50 Denoted by D 3 The average particle size D of particle D 50 Denoted by D 4 Denoted by D 1 > D 2 > D 3 > D4 where 1.5 μm ≤ D 1 ≤ 2.5 μm; and D 2 / D 1 = a, D 3 / D 1 = b, D 4 / D 1 = c, where the value range of a is 0.36 - 0.80, the value range of b is 0.20 - 0.54, and the value range of c is 0.10 - 0.24; then mix particles A, B, C, and D according to a mass ratio of 1 - 50:10 - 40:20 - 50:50 - 70 to obtain a precursor mixed slurry, and perform a drying treatment on the precursor mixed slurry to obtain an intermediate; perform three-stage sintering on the intermediate in an atmosphere of a protective gas, and the sintering temperature of the three-stage sintering increases successively to prepare lithium iron phosphate, wherein, in the three-stage sintering, the sintering temperature of the first-stage sintering is 300 - 450 °C, and the sintering time is not less than 1 hour. For example, a is 0.36, 0.40, 0.45, 0.50, 0.55, 0.60, 0.65, 0.70, 0.75, or 0.80, etc., b is 0.20, 0.25, 0.30, 0.35, 0.40, 0.45, 0.50, or 0.54, etc., c is 0.10, 0.15, 0.20, or 0.24, etc.; the mass ratio of particles A, B, C, and D is 1:10:20:69, 20:10:20:50, 10:15:20:55, 40:5:5:50, etc.

[0006] In the preparation method of lithium iron phosphate provided by the present invention, by grinding the raw materials into a mixture with four different particle size ranges and then undergoing three-stage sintering, a lithium iron phosphate material with a high tap density and a large rate capacity can be prepared. First, using raw materials that meet the above particle size requirements and ratio relationships can effectively control the particle size distribution of the raw materials, enabling a relatively dense packing between the raw materials. This not only makes the prepared lithium iron phosphate have a high tap density and rate capacity, but also enables sufficient contact between iron phosphate, lithium source, and carbon source, which is beneficial to improving the purity of lithium iron phosphate and enhancing the cycle performance and energy density of the lithium iron phosphate material. Second, during the three-stage sintering process, the heat transfer times required for the raw materials with the above particle size requirements are relatively consistent, which is more conducive to controlling the reaction process. During the first-stage sintering process, a sintering temperature of 300-450°C is used for heat preservation. During this stage of heat preservation, the carbon source will first be melted into a liquid state, and then carbon atoms will collide with metal atoms to form a carbon microcrystalline structure, which is beneficial to the full decomposition of the carbon source and uniform coating on the surface of the particles, preventing the particles from contacting each other, and is beneficial to maintaining the distribution relationship between different particle size gradations of the precursor mixed particles, that is, the values of a, b, and c still satisfy the above range, avoiding a large number of melting crystals during subsequent high-temperature sintering. During the second-stage sintering and third-stage sintering processes where the sintering temperature increases sequentially, the lithium source and iron phosphate decompose and recombine to form a lithium iron phosphate material with a stable structure. Among them, the second-stage heat preservation is beneficial to improving the rate performance, and the third-stage high-temperature heat preservation is beneficial to increasing the tap density of the material. In summary, using 4 kinds of particles that meet the above particle size relationship and ratio, the lithium iron phosphate prepared after three-stage sintering is beneficial to improving the tap density and rate capacity of lithium iron phosphate, thereby enhancing the energy density and cycle stability of the battery using this lithium iron phosphate as the cathode material.

[0007] Preferably, the specific operation of preparing the precursor mixed slurry includes: mixing iron phosphate, lithium source, carbon source, and solvent to obtain the precursor mixed slurry.

[0008] Preferably, the specific operation of regulating the particle size of the particles in the precursor mixed slurry includes: grinding the precursor mixed slurry to obtain particle A; taking a part of particle A and grinding it to obtain particle B; taking a part of particle B and grinding it to obtain particle C; taking a part of particle C and grinding it to obtain particle D.

[0009] Preferably, the grinding includes ball milling.

[0010] Preferably, the average particle size D of the intermediate 50 is 10-40 μm. For example, the average particle size D of the intermediate 50 is 10 μm, 15 μm, 20 μm, 25 μm, 30 μm, 35 μm, 40 μm.

[0011] Preferably, the value range of a is 0.38 to 0.60, the value range of b is 0.20 to 0.30, and the value range of c is 0.16 to 0.24. For example, a is 0.38, 0.42, 0.48, 0.52, 0.58, 0.60, etc., b is 0.20, 0.22, 0.28, 0.30, etc., and c is 0.16, 0.18, 0.20, 0.22, 0.24. When the values of a, b, and c satisfy the above ranges, not only can particles A, B, C, and D form a relatively dense packing by means of different particle size gradings, improving the tap density of lithium iron phosphate, but also the migration path of lithium ions can be regulated, enhancing the transport rate of lithium ions in lithium iron phosphate and improving the rate performance.

[0012] Preferably, the mass percentages of particles A, B, C, and D in the precursor mixed slurry satisfy: the sum of the masses of particles A and D > the sum of the masses of particles B and C. By comprehensively regulating the particle size distribution and mass percentage of the above four mixtures, the tortuosity of the lithium ion transport path can be controlled within a suitable range, achieving both an increase in the lithium ion transport rate and an increase in the tap density of the prepared lithium iron phosphate.

[0013] Preferably, in the precursor mixed slurry, the mass ratio of particles A, B, C, and D is 5:30:15:60.

[0014] Preferably, in the precursor mixed slurry, the mass ratio of iron phosphate, lithium source, and carbon source is 28.0 to 35.0:6.0 to 10:3.0 to 5.0.

[0015] Preferably, in the precursor mixed slurry, the mass ratio of iron phosphate, lithium source, and carbon source is 31:8:3.3.

[0016] Preferably, the mass percentage of the carbon source in the precursor mixed slurry is 3.0 to 5.0 wt%. For example, the mass percentage of the carbon source in the precursor mixed slurry is 3.0 wt%, 3.5 wt%, 4.0 wt%, 4.5 wt%, 5.0 wt%, etc. When the mass percentage of the carbon source falls within the above range, it can promote the formation of a uniformly coated carbon layer on the surface of the above four mixtures during the sintering process, and the carbon layer has an appropriate thickness, which can not only improve the electrical conductivity between lithium iron phosphate particles but also maintain a high energy density in the final lithium iron phosphate product.

[0017] Preferably, the solid content of the precursor mixed slurry is 30 to 40%. For example, the solid content of the precursor mixed slurry is 30%, 35%, 40%, etc.

[0018] Preferably, the molar ratio of iron element to phosphorus element in iron phosphate is 0.97 to 0.98. More preferably, the molar ratio of iron element to phosphorus element in iron phosphate is 0.975.

[0019] Preferably, the lithium source includes at least one of lithium carbonate, lithium hydroxide, lithium nitrate, lithium oxalate, lithium acetate, and lithium dihydrogen phosphate.

[0020] Preferably, the carbon source includes at least one of organic carbon and inorganic carbon.

[0021] Preferably, the organic carbon includes at least one of glucose, sucrose, polyethylene glycol, phenolic resin, polyethylene glycol octyl phenyl ether, polyvinylpyrrolidone, ethanol, methanol, formaldehyde, toluene, acetone, methane, ethylene, and acetylene.

[0022] Preferably, the inorganic carbon includes at least one of graphene, carbon nanotubes, and conductive nanosheets.

[0023] Preferably, in the three-stage sintering, the holding time of the first-stage sintering is 1 to 4 hours. For example, the holding time of the first-stage sintering is 1 hour, 2 hours, 3 hours, 4 hours, etc.

[0024] Preferably, in the three-stage sintering, the temperature of the second-stage sintering is 550 to 700 °C. For example, the temperature of the second-stage sintering is 550 °C, 600 °C, 650 °C, 700 °C, etc. During the second-stage sintering, iron phosphate and the carbon source are gradually decomposed and recombined to form lithium iron phosphate. Using a sintering temperature of 500 to 700 °C is beneficial to improving the structural stability and rate performance of lithium iron phosphate.

[0025] Preferably, in the three-stage sintering, the holding time of the second-stage sintering is 2 to 4 hours. For example, the holding time of the second-stage sintering is 2 hours, 3 hours, 4 hours, etc.

[0026] Preferably, in the three-stage sintering, the temperature of the third-stage sintering is 750 to 800 °C. For example, the temperature of the third-stage sintering is 750 °C, 760 °C, 780 °C, 790 °C, 800 °C, etc. During the third-stage sintering, using a sintering temperature of 750 to 800 °C, the crystallinity of lithium iron phosphate is improved, the graphitization degree of the carbon layer increases, and the lithium iron phosphate particles further grow, which is beneficial to improving the tap density and rate capacity of lithium iron phosphate.

[0027] Preferably, in the three-stage sintering, the holding time of the third-stage sintering is 7 to 15 hours. For example, the holding time of the third-stage sintering is 7 hours, 8 hours, 9 hours, 10 hours, 11 hours, 12 hours, 13 hours, 14 hours, 15 hours, etc.

[0028] Preferably, the total sintering time of the three-stage sintering is not higher than 16 hours.

[0029] Preferably, the precursor mixed slurry further comprises an antioxidant, and the antioxidant comprises an organic acid. Introducing an antioxidant into the precursor mixed slurry can improve the agglomeration of particles in the precursor mixed slurry and reduce the slurry viscosity, which is helpful for subsequent operation steps.

[0030] Preferably, the antioxidant comprises at least one of citric acid, ascorbic acid, and phthalic acid.

[0031] Preferably, the mass ratio of the antioxidant in the precursor mixed slurry is 0.6 - 1.0 wt‰. For example, the mass ratio of the antioxidant in the precursor mixed slurry is 0.6 wt‰, 0.7 wt‰, 0.8 wt‰, 0.9 wt‰, 1.0 wt‰, etc.

[0032] Preferably, the precursor mixed slurry further comprises a dopant, and the doping elements of the dopant comprise at least one of titanium, magnesium, aluminum, niobium, and vanadium.

[0033] Preferably, the feeding amount of the dopant is such that the total addition amount of the doping elements in the precursor mixed slurry is not higher than 2800 ppm.

[0034] Preferably, the dopant comprises at least one of titanium dioxide, magnesium oxide, aluminum oxide, niobium pentoxide, vanadium trioxide, and ammonium metavanadate.

[0035] According to the second aspect of the present invention, there is provided a lithium iron phosphate prepared by using the preparation method of lithium iron phosphate described above.

[0036] Preferably, the particle size D of the lithium iron phosphate 50 is 0.5 - 2.0 μm. For example, the particle size D of the lithium iron phosphate 50 is 0.5 μm, 1.0 μm, 1.5 μm, 2.0 μm, etc.

[0037] According to the third aspect of the present invention, there is provided an electrode sheet, comprising a current collector and an active material, and the active material comprises the above-mentioned lithium iron phosphate.

[0038] According to the fourth aspect of the present invention, there is provided a battery, comprising a positive electrode, a negative electrode, and an electrolyte, and the positive electrode comprises the above-mentioned electrode sheet. Detailed Embodiments

[0039] In order to enable those skilled in the art to better understand the technical solutions in the present invention, the technical solutions of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only a part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without creative efforts shall fall within the protection scope of the present invention.

[0040] Example 1

[0041] This example provides a lithium iron phosphate, and its preparation raw materials include iron phosphate, a lithium source, a carbon source, an antioxidant, a dopant and a solvent. Among them, the molar ratio of iron element to phosphorus element in the iron phosphate is 0.975, the lithium source is selected as lithium carbonate, the carbon source is selected as glucose and polyethylene glycol, the antioxidant is selected as citric acid, and the dopant is selected as titanium dioxide.

[0042] The specific preparation method includes the following steps:

[0043] S1. Prepare a precursor mixed slurry: First, mix iron phosphate, a lithium source, a carbon source, an antioxidant, a dopant and a solvent to obtain a precursor mixed slurry. Among them, the feeding mass of the above-mentioned preparation raw materials meets the following requirements: the mass ratio of iron phosphate, the lithium source and the carbon source is 31:8:3.3, the mass proportion of the antioxidant in the precursor mixed slurry is 0.8 wt‰, the feeding amount of the dopant makes the total addition amount of the doped element titanium in the precursor mixed slurry 1300 ppm; the feeding amount of the solvent makes the solid content of the precursor mixed slurry 40%.

[0044] S2. Adjust the particle size of the particles in the precursor mixed slurry: Grind the precursor mixed slurry to obtain particle A, take a part of particle A and grind it to obtain particle B, take a part of particle B and grind it to obtain particle C, and take a part of particle C and grind it to obtain particle D. Among them, the average particle size D 50 is represented by D 1 ; the average particle size D 50 of particle B is represented by D 2 ; the average particle size D 50 of particle C is represented by D 3 ; the average particle size D 50 of particle D is represented by D 4 . In this example, D 1 is 2.0 μm, D 2 is 0.83 μm, D 3 is 0.45 μm, D 4 is 0.354 μm. From this, it can be calculated that: D 1 > D 2 > D 3 > D 4 , D 2 / D 1 = a = 0.414, D 3 / D 1 = b = 0.225, D 4 / D 1 = c = 0.177.

[0045] S3. Preparation of Intermediate: Then, mix Granule A, Granule B, Granule C, and Granule D evenly according to the mass ratio of 5:30:15:60 to obtain a precursor mixed slurry; subject the precursor mixed slurry to spray drying to obtain an intermediate with an average particle size D 50 of 25 μm.

[0046] S4. Sintering: Sinter the intermediate in a protective gas atmosphere in three stages to obtain lithium iron phosphate. Among them, the specific operations for the three-stage sintering are as follows: First, the sintering temperature for the first-stage sintering is 400 °C, and the sintering time is 2.5 hours. Then, raise the temperature to the sintering temperature of 650 °C for the second-stage sintering, and the sintering time is 3 hours. Subsequently, continue to raise the temperature to the sintering temperature of 780 °C for the third-stage sintering, and the sintering time is 9 hours.

[0047] S5. Post-treatment: Classify and crush the lithium iron phosphate to obtain a lithium iron phosphate product with a D50 particle size of 1.3 μm, and the particle size distribution width of this lithium iron phosphate product ≤ 12.

[0048] In other embodiments, according to the actual situation, the types and dosages of iron phosphate, lithium source, carbon source, antioxidant, and dopant can be adjusted, or the sintering temperature and sintering time of the three-stage sintering can be adjusted.

[0049] Example 2

[0050] This example refers to the preparation method of lithium iron phosphate provided in Example 1 to prepare a kind of lithium iron phosphate. The difference between this example and Example 1 is that: in the process of S2 for preparing lithium iron phosphate, the average particle sizes of Granule B, Granule C, and Granule D are adjusted so that a = 0.80, b = 0.54, and c = 0.24. That is, D 1 is 2.0 μm, D 2 is 1.6 μm, D 3 is 1.08 μm, D 4 is 0.48 μm. The other raw material ratios and preparation methods are strictly the same as those in Example 1.

[0051] Example 3

[0052] This example refers to the preparation method of lithium iron phosphate provided in Example 1 to prepare a kind of lithium iron phosphate. The difference between this example and Example 1 is that: in the process of S2 for preparing lithium iron phosphate, the average particle sizes of Granule B, Granule C, and Granule D are adjusted so that a = 0.60, b = 0.30, and c = 0.20. That is, D 1 is 2.0 μm, D 2 is 1.2 μm, D 3 is 0.6 μm, D 4 is 0.40 μm. The other raw material ratios and preparation methods are strictly the same as those in Example 1.

[0053] Example 4

[0054] This example refers to the preparation method of lithium iron phosphate provided in Example 1 to prepare a kind of lithium iron phosphate. The difference between this example and Example 1 is that in the S2 process of preparing lithium iron phosphate, the average particle sizes of particle B, particle C, and particle D are adjusted so that a = 0.38, b = 0.20, and c = 0.16. That is, D 1 is 2.0 μm, D 2 is 0.76 μm, D 3 is 0.4 μm, D 4 is 0.32 μm. The rest of the raw material ratios and preparation methods are strictly the same as those in Example 1.

[0055] Example 5

[0056] This example refers to the preparation method of lithium iron phosphate provided in Example 1 to prepare a kind of lithium iron phosphate. The difference between this example and Example 1 is that in the S2 process of preparing lithium iron phosphate, the average particle sizes of particle B, particle C, and particle D are adjusted so that a = 0.36, b = 0.20, and c = 0.10. That is, D 1 is 2.0 μm, D 2 is 0.72 μm, D 3 is 0.40 μm, D 4 is 0.20 μm. The rest of the raw material ratios and preparation methods are strictly the same as those in Example 1.

[0057] Example 6

[0058] This example refers to the preparation method of lithium iron phosphate provided in Example 1 to prepare a kind of lithium iron phosphate. The difference between this example and Example 1 is that in the S3 process of preparing lithium iron phosphate, the mixing ratio of particle A, particle B, particle C, and particle D is adjusted to 1:10:20:69. The rest of the raw material ratios and preparation methods are strictly the same as those in Example 1.

[0059] Example 7

[0060] This example refers to the preparation method of lithium iron phosphate provided in Example 1 to prepare a kind of lithium iron phosphate. The difference between this example and Example 1 is that in the S3 process of preparing lithium iron phosphate, the mixing ratio of particle A, particle B, particle C, and particle D is adjusted to 20:10:20:50. The rest of the raw material ratios and preparation methods are strictly the same as those in Example 1.

[0061] Example 8

[0062] This example refers to the preparation method of lithium iron phosphate provided in Example 1 to prepare a kind of lithium iron phosphate. The difference between this example and Example 1 is that in the S4 process of preparing lithium iron phosphate, the sintering temperature of the first-stage sintering is adjusted to 300 °C. The other raw material ratios and preparation methods are strictly the same as those in Example 1.

[0063] Example 9

[0064] This example refers to the preparation method of lithium iron phosphate provided in Example 1 to prepare a kind of lithium iron phosphate. The difference between this example and Example 1 is that in the S4 process of preparing lithium iron phosphate, the sintering temperature of the first-stage sintering is adjusted to 450 °C. The other raw material ratios and preparation methods are strictly the same as those in Example 1.

[0065] Example 10

[0066] This example refers to the preparation method of lithium iron phosphate provided in Example 1 to prepare a kind of lithium iron phosphate. The difference between this example and Example 1 is that in the S4 process of preparing lithium iron phosphate, the sintering temperature of the second-stage sintering is adjusted to 500 °C. The other raw material ratios and preparation methods are strictly the same as those in Example 1.

[0067] Example 11

[0068] This example refers to the preparation method of lithium iron phosphate provided in Example 1 to prepare a kind of lithium iron phosphate. The difference between this example and Example 1 is that in the S4 process of preparing lithium iron phosphate, the sintering temperature of the second-stage sintering is adjusted to 750 °C. The other raw material ratios and preparation methods are strictly the same as those in Example 1.

[0069] Example 12

[0070] This example refers to the preparation method of lithium iron phosphate provided in Example 1 to prepare a kind of lithium iron phosphate. The difference between this example and Example 1 is that in the S4 process of preparing lithium iron phosphate, the sintering temperature of the third-stage sintering is adjusted to 700 °C. The other raw material ratios and preparation methods are strictly the same as those in Example 1.

[0071] Example 13

[0072] This example refers to the preparation method of lithium iron phosphate provided in Example 1 to prepare a kind of lithium iron phosphate. The difference between this example and Example 1 is that in the S4 process of preparing lithium iron phosphate, the sintering temperature of the third-stage sintering is adjusted to 900 °C. The other raw material ratios and preparation methods are strictly the same as those in Example 1.

[0073] Comparative Example 1

[0074] This comparative example refers to the preparation method of lithium iron phosphate provided in Example 1 to prepare a kind of lithium iron phosphate. The difference between this comparative example and Example 1 is that in the S2 process of preparing lithium iron phosphate, equal-mass particles A with an average particle size of 3.6 μm are used, and the particle size relationship of a = 0.414, b = 0.225, and c = 0.177 is maintained, and the average particle sizes of particles B, C, and D are adjusted. That is, D 1 is 3.6 μm, D 2 is 1.49 μm, D 3 is 0.81 μm, D 4 is 0.64 μm. The other raw material ratios and preparation methods are strictly the same as those in Example 1.

[0075] Comparative Example 2

[0076] This comparative example refers to the preparation method of lithium iron phosphate provided in Example 1 to prepare a kind of lithium iron phosphate. The difference between this comparative example and Example 1 is that in the S2 process of preparing lithium iron phosphate, equal-mass particles D are used to replace particles A, B, and C in Example 1. The other raw material ratios and preparation methods are strictly the same as those in Example 1.

[0077] Comparative Example 3

[0078] This comparative example refers to the preparation method of lithium iron phosphate provided in Example 1 to prepare a kind of lithium iron phosphate. The difference between this comparative example and Example 1 is that in the S4 process of preparing lithium iron phosphate, the sintering temperature of the first-stage sintering is adjusted to 250 °C. The other raw material ratios and preparation methods are strictly the same as those in Example 1.

[0079] Comparative Example 4

[0080] This comparative example refers to the preparation method of lithium iron phosphate provided in Example 1 to prepare a kind of lithium iron phosphate. The difference between this comparative example and Example 1 is that in the S4 process of preparing lithium iron phosphate, the sintering temperature of the first-stage sintering is adjusted to 500 °C. The other raw material ratios and preparation methods are strictly the same as those in Example 1.

[0081] Comparative Example 5

[0082] This example refers to the preparation method of lithium iron phosphate provided in Example 1 to prepare a kind of lithium iron phosphate. The difference between this example and Example 1 is that in the S3 process of preparing lithium iron phosphate, the mixing ratio of particles A, B, C, and D is adjusted to 25:25:25:25. The other raw material ratios and preparation methods are strictly the same as those in Example 1.

[0083] Comparative Example 6

[0084] This example refers to the preparation method of lithium iron phosphate provided in Example 1 to prepare a kind of lithium iron phosphate. The difference between this example and Example 1 is that in the process of S3 for preparing lithium iron phosphate, the mixing ratio of particle A, particle B, particle C and particle D is adjusted to 1:10:55:85. The other raw material ratios and preparation methods are strictly the same as those in Example 1.

[0085] Test Example

[0086] Test objects: Lithium iron phosphate provided in Examples 1 to 13 and Comparative Examples 1 to 6.

[0087] Test items and test methods:

[0088] (1) Compaction density: Using Sansi Zongheng equipment, weigh 0.8 g of lithium iron phosphate sample and load it into the mold, and perform compaction test with a force of 3 N, and record the compaction density.

[0089] (2) Rate capacity: Prepare a button cell using the above-mentioned test objects as the positive electrode active material, and perform constant current charge and discharge on the battery for one week at different currents (0.1C, 0.5C, 1.0C) at 25 °C, and record the discharge capacity Q of the battery at different currents 0.1C 、Q 0.5C 、Q 1C ; among them, the voltage range is 2.0 V to 3.75 V.

[0090] Among them, the preparation operation of the lithium-ion battery includes: using the above-mentioned test objects as the positive electrode active material for the positive electrode, and using polyvinylidene fluoride (PVDF) as the positive electrode binder; using a lithium sheet for the negative electrode and a polyethylene separator for the separator. Stack the positive electrode, separator, and negative electrode in sequence to obtain a button cell.

[0091] Test results: The test results in this test example are shown in Table 1.

[0092] Table 1. Compaction density and rate capacity measured for each test object

[0093]

[0094] Result analysis:

[0095] Comparing the test performances of Examples 1 to 13 and Comparative Examples 1 to 6 in Table 1, it can be found that compared with the lithium iron phosphate materials provided in Comparative Examples 1 to 6, the lithium iron phosphate materials provided in Examples 1 to 13 have a higher compaction density and a larger rate capacity.

[0096] Comparing the lithium iron phosphate and batteries provided in Examples 1 to 5 and Comparative Examples 1 to 2, it can be found that the compaction density of the lithium iron phosphate provided in Examples 1 to 5 is not lower than 2.59 g / cm 3 ,and the discharge capacity Q of the battery1C Not less than 139.6 mAh / g. This shows that during the preparation of lithium iron phosphate, the particle size of the particles in the precursor mixed slurry is regulated, so that the D of particle A, particle B, particle C, and particle D 50 satisfies: D 1 > D 2 > D 3 > D 4 , 1.5 μm ≤ D 1 ≤ 2.5 μm; and D 2 / D 1 = a, D 3 / D 1 = b, D 4 / D 1 = c, a is 0.36 - 0.80, b is 0.20 - 0.54, c is 0.10 - 0.24. Thus, the particle size distribution of the raw materials can be effectively controlled, enabling the raw materials to form a relatively dense packing, and making the prepared lithium iron phosphate have a high tap density and rate capacity. Among them, compared with the case where D 1 > 2.5 μm in Comparative Example 1, the D of particle A, particle B, particle C, and particle D in Examples 1 - 5 50 matches the mass ratio of particle A, particle B, particle C, and particle D. Therefore, the batteries of Examples 1 - 5 have a rate capacity higher than that of the battery in Comparative Example 1. Compared with the lithium iron phosphate prepared only with particle D in Comparative Example 2, particle A, particle B, particle C, and particle D in Examples 1 - 5 can have a high discharge capacity on the premise of forming a relatively dense packing, while the tap density of the lithium iron phosphate prepared only with particle D is small. Secondly, among the lithium iron phosphates provided in Examples 1 - 5, the comprehensive performance of Examples 1, 3 - 4 is better than that of Examples 2, 5. This shows that when the value range of a is 0.38 - 0.60, the value range of b is 0.20 - 0.30, and the value range of c is 0.16 - 0.24, the prepared lithium iron phosphate can simultaneously achieve a high tap density and a large discharge capacity.

[0097] Comparing the lithium iron phosphate and batteries provided by Examples 1, 8 - 9 with those provided by Comparative Examples 3 - 4, it can be found that as the temperature of the first - stage sintering rises, the tap density and rate capacity of the prepared lithium iron phosphate show a trend of first rising and then falling. Among them, the tap density of the lithium iron phosphate provided by Examples 1 and 8 - 9 and the rate capacity of the battery are better than the comprehensive performance of the lithium iron phosphate provided by Comparative Examples 3 - 4. This shows that when the temperature of the first - stage sintering is 300 - 450 °C, it is beneficial for the precursor mixed particles to maintain the distribution relationship between different particle size gradations, thereby making the prepared lithium iron phosphate have a high tap density and a large discharge capacity.

[0098] Comparing the lithium iron phosphate and batteries provided in Example 1, Examples 6-7 and Comparative Examples 5-6, it can be found that the comprehensive performance of the lithium iron phosphate provided in Example 1 and Examples 6-7 is superior to that of the lithium iron phosphate provided in Comparative Examples 5-6. This shows that when the particles A, B, C and D are mixed in a ratio of 1-50:10-40:20-50:50-70, they can match with the D of the particles A, B, C and D 50 to form a relatively dense packing, and lithium iron phosphate with a high tap density and good rate capacity can be prepared.

[0099] The above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit the protection scope of the present invention. Although the present invention has been described in detail with reference to the preferred embodiments, those of ordinary skill in the art should understand that the technical solutions of the present invention can be modified or equivalently replaced without departing from the essence and scope of the technical solutions of the present invention.

Claims

1. A method for preparing lithium iron phosphate, characterized in that: The following steps are involved: A precursor mixed slurry containing iron phosphate, a lithium source, and a carbon source is prepared, and the particle size of the particles in the precursor mixed slurry is controlled to obtain particles A, particles B, particles C, and particles D. The average particle size of particles A is D 50 The average particle size D of the particles B is represented by D1. 50 The average particle size D of the particles C is represented by D2. 50 The average particle size D of the particles D is represented by D3. 50 Expressed as D4, D1>D2>D3>D4, 1.5μm≤D1≤2.5μm; and D2 / D1=a, D3 / D1=b, D4 / D1=c, the value range of a is 0.36~0.80, the value range of b is 0.20~0.54, and the value range of c is 0.10~0.24; Then, the particles A, B, C and D are mixed in a mass ratio of 1-50:10-40:20-50:50-70 to obtain a precursor mixed slurry, and the precursor mixed slurry is dried to obtain an intermediate; The intermediate is sintered in three stages in a protective gas atmosphere, and the sintering temperatures of the three stages are increased successively to prepare the lithium iron phosphate, wherein, in the three stages of sintering, the sintering temperature of the first stage is 300-450° C., and the sintering time is not less than 1 hour.

2. The method for preparing lithium iron phosphate according to claim 1, characterized in that: The value range of a is 0.38-0.60, the value range of b is 0.20-0.30, and the value range of c is 0.16-0.

20.

3. The method for preparing lithium iron phosphate according to claim 1, characterized in that: The mass proportions of the particles A, B, C and D in the precursor mixed slurry satisfy: the sum of the masses of the particles A and D>the sum of the masses of the particles B and C.

4. The method for preparing lithium iron phosphate according to claim 1, characterized in that: In the precursor mixed slurry, the mass ratio of the iron phosphate, the lithium source and the carbon source is 28.0-35.0:6.0-10.0:3.0-5.

0.

5. The method for preparing lithium iron phosphate according to claim 4, characterized in that: The mass proportion of the carbon source in the precursor mixed slurry is 3.0-5.0 wt %.

6. The method for preparing lithium iron phosphate according to claim 1, characterized in that: In the three-stage sintering, the sintering temperature of the second stage sintering is 550-700°C.

7. The method for preparing lithium iron phosphate according to claim 1, characterized in that: In the three-stage sintering, the sintering temperature of the third stage sintering is 750-800°C.

8. The method for preparing lithium iron phosphate according to any one of claims 1 to 7, characterized in that: The precursor mixed slurry further includes an antioxidant, and the antioxidant includes an organic acid.

9. Lithium iron phosphate prepared by the method for preparing lithium iron phosphate according to any one of claims 1 to 8.

10. A pole piece, characterized in that: It comprises a current collector and an active material, wherein the active material comprises the lithium iron phosphate as claimed in claim 9.

11. A battery, characterized in that: It comprises a positive electrode, a negative electrode and an electrolyte, wherein the positive electrode comprises the electrode sheet as claimed in claim 10.